2013
DOI: 10.1016/j.drugalcdep.2013.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood socioeconomic status and substance use by U.S. adults

Abstract: Background This study examined relationships of extremes in neighborhood socioeconomic status with use of tobacco, alcohol, marijuana and other drugs. Hypotheses were (1) residence in disadvantaged neighborhoods would be positively associated with stress-related and higher-risk substance use patterns (e.g., drug use), and (2) residence in affluent neighborhoods would be positively associated with “healthy” substance use (e.g., drinking within recommended guidelines) and negatively associated with substance use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 76 publications
5
70
0
2
Order By: Relevance
“…We first showed that an increase in the frequency of relocations was associated with numerous other risk factors. Those who relocated in childhood were more likely to have been born to young parents and have parents who abuse substances, have lower incomes, and engage in criminal activity, which supports previous research (Dohrenwend et al , 1992, Karriker-Jaffe, 2013, US Census Bureau, 2013). We then utilized analyses to incorporate both measured covariates and family-based comparisons, including the comparison of differentially exposed cousins and siblings.…”
Section: Discussionsupporting
confidence: 85%
“…We first showed that an increase in the frequency of relocations was associated with numerous other risk factors. Those who relocated in childhood were more likely to have been born to young parents and have parents who abuse substances, have lower incomes, and engage in criminal activity, which supports previous research (Dohrenwend et al , 1992, Karriker-Jaffe, 2013, US Census Bureau, 2013). We then utilized analyses to incorporate both measured covariates and family-based comparisons, including the comparison of differentially exposed cousins and siblings.…”
Section: Discussionsupporting
confidence: 85%
“…The majority of stigmatised behaviours included in the considered cases—cigarette use, various kinds of substance abuse, poor eating habits—are taken up most frequently by those at the bottom of the socioeconomic hierarchy 55–57. Interestingly, alcoholism does appear to spread itself fairly evenly across tax brackets,58 but unremitting alcoholism is associated with disadvantaged neighbourhoods 59. Many of these behaviours co-occur with psychiatric illnesses, and especially so in the least well off 60.…”
Section: Improved Health Outcomesmentioning
confidence: 99%
“…The main finding is that inhabitants of socio-economically disadvantaged areas have increased risks for daily smoking, heavy alcohol use and the use of hard illegal drugs (Blomgren et al, 2004, Cerda et al, 2010, Karriker-Jaffe, 2013, Martikainen et al, 2003. Theories of social marginalization and deprivation (for a summary, see Sampson, 2011) suggest that socio-economically poor areas may suffer from a lack of 'collective efficacy', poor policing and schools that fail to maintain social order.…”
Section: Two Emerging Traditions Of Area-based Substance Use Studiesmentioning
confidence: 99%
“…Actually, few studies address living conditions and sociocultural aspects of lifestyles in areas inhabited by those with middle and high levels of education and income (Sampson, 2011, Sampson et al, 2015, and some studies even suggest that adolescents in such areas may have specific risk factors for maladaptive outcomes (Luthar, 2003). Moreover, all psychosocial problems may not necessarily follow the typical pattern of a concentration in areas of disadvantage, and there is increasing evidence that this may be true for the use of psychoactive substances , Karriker-Jaffe, 2011, Karriker-Jaffe, 2013). Here we ask: To what degree does the use of such substances reflect the socio-economic characteristics of a certain area?…”
Section: Introductionmentioning
confidence: 99%